2017
DOI: 10.1093/femsle/fnx008
|View full text |Cite
|
Sign up to set email alerts
|

E152A substitution drastically affects NDM-5 activity

Abstract: New Delhi Metallo beta-lactamase (NDM) is of significant public health concern due to its enormous potential to hydrolyse all major beta-lactams including carbapenems. Amino acid substitutions outside the active site reportedly affect NDM beta-lactamase activities. Here, the effect of amino acid substitutions in the possible omega-like loop region of NDM-5 has been elucidated. Overall, three substitution mutations near active site of NDM-5 were done, namely, E152A, S191A and D223A and subsequently, the change … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…The overproduced soluble proteins with His 6 tag were purified by Ni-nitrilotriacetic acid (NTA)-based affinity chromatography with minor protein-specific optimizations as necessary ( Fig. S4 ) ( 70 72 ). Proteins that were not soluble were treated with 1% sarkosyl at room temperature with constant low-speed shaking and followed by sonication similar to other soluble proteins.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The overproduced soluble proteins with His 6 tag were purified by Ni-nitrilotriacetic acid (NTA)-based affinity chromatography with minor protein-specific optimizations as necessary ( Fig. S4 ) ( 70 72 ). Proteins that were not soluble were treated with 1% sarkosyl at room temperature with constant low-speed shaking and followed by sonication similar to other soluble proteins.…”
Section: Methodsmentioning
confidence: 99%
“…The reaction was monitored at 496 nm for 120 min, 25°C. Kinetic parameters of the enzymes were determined by methods described earlier ( 25 , 70 ).…”
Section: Methodsmentioning
confidence: 99%
“…Other clinically relevant carbapenemases include MBLs that belong to subclass B1: Verona Integron-encoded MBLs (VIM) and imipenemase (IMP) ( 34 , 43 ). As carbapenemases spread within Enterobacteriaceae , amino acid substitutions occur, producing different variants of the carbapenemase.…”
Section: Carbapenemase Productionmentioning
confidence: 99%
“…As carbapenemases spread within Enterobacteriaceae , amino acid substitutions occur, producing different variants of the carbapenemase. This results in changes in the carbapenemase activity and its affinity to carbapenems ( 43 ). Paul et al ( 44 ) showed that NDM variants (NDM-1 and NDM-5) had different transcriptional responses to different carbapenems, where NDM-5 had a 10-fold increase in expression when exposed to ertapenem, and NDM-1 had only a 2-fold increase.…”
Section: Carbapenemase Productionmentioning
confidence: 99%
“…The cross-linking was initially studied with purified NDM-5 30 under nonreducing conditions in which the protein exists both as monomeric and dimeric forms 28,29 in solution as revealed by the appearance of two distinct bands under CBB at ∼26 and ∼50 kDa corresponding to the mono and dimeric forms, respectively. All the probes were incubated with both NDM-5 and NDM-7 under irradiation with UV.…”
Section: Resultsmentioning
confidence: 99%